Investing on the Polish Market of Condo-Hotels and Apart-Hotels – Selected Legal Issues - Badura, Ewelina (Review of European and Comparative Law, 2021)
The institutions of a condo-hotel and apart-hotel are not defined in Polish legislation. However, ownership issues of such facilities are not entirely outside statutory regulations. Legal diversity, the absence of an unambiguous definition and of transparent statistical data, combined with the interchangeable use of the terms “condo-hotel” and “apart-hotel” by investors and operators of such facilities may raise concerns about the proper functioning of the market for this type of investment in Poland. The risks of investing in condo-hotels and apart-hotels in Poland can be divided into several basic categories.